Living on the edge: the rise of job insecurity in modern Britain (London, 2016)
"Ten years ago the TUC established a Commission on Vulnerable Employment (CoVE), to examine the increase in the proportion of workers at risk of poverty and injustice due to an imbalance of power in the employer-worker relationship.